1998
DOI: 10.1086/301901
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Association of Apolipoprotein E with Age-Related Macular Degeneration

Abstract: Age-related macular degeneration (AMD) is the most common geriatric eye disorder leading to blindness and is characterized by degeneration of the neuroepithelium in the macular area of the eye. Apolipoprotein E (apoE), the major apolipoprotein of the CNS and an important regulator of cholesterol and lipid transport, appears to be associated with neurodegeneration. The apoE gene (APOE) polymorphism is a strong risk factor for various neurodegenerative diseases, and the apoE protein has been demonstrated in dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
274
5
4

Year Published

2001
2001
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 407 publications
(301 citation statements)
references
References 53 publications
13
274
5
4
Order By: Relevance
“…Interestingly, the E4 allele has been reported by several independent groups as being significantly less prevalent among AMD cases when compared with the corresponding control populations [Klaver et al, 1998a;Souied et al, 1998;Simonelli et al, 2001;Baird et al, 2004;Zareparsi et al, 2004]. The E4 polymorphism is associated with a protective effect against AMD, while the E2 allele is weakly associated with a slightly increased risk for developing late AMD (see our meta-analysis).…”
Section: Introductionsupporting
confidence: 50%
See 2 more Smart Citations
“…Interestingly, the E4 allele has been reported by several independent groups as being significantly less prevalent among AMD cases when compared with the corresponding control populations [Klaver et al, 1998a;Souied et al, 1998;Simonelli et al, 2001;Baird et al, 2004;Zareparsi et al, 2004]. The E4 polymorphism is associated with a protective effect against AMD, while the E2 allele is weakly associated with a slightly increased risk for developing late AMD (see our meta-analysis).…”
Section: Introductionsupporting
confidence: 50%
“…The E4 isoform is also associated with various neurodegenerative diseases, most notably Alzheimer Disease (AD) [Chapman et al, 2001;Laws et al, 2003]. Cardiovascular disease, AD, and AMD share a number of similar pathological features [Klaver et al, 1998a[Klaver et al, ,1999Mullins et al, 2000;Dentchev et al, 2003]. ApoE is also a ubiquitous component of soft drusen, a hallmark of early AMD development [Anderson et al, 2001].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…C'est aussi une protéine chaperonne importante dans le cytoplasme des cellules. C'était donc un possible gène candidat et deux études respectivement menées par Souied et al et Klaver et al en 1998 ont conclu à son association à la DMLA [7,8]. Dans ces deux études, l'isoforme 4 apparaît comme protectrice, avec des odds ratio respectifs de 0,34 et 0,43.…”
Section: Les Gènes De Susceptibilité à La Dmla Récemment Identifiésunclassified
“…For instance, large amounts of lipids are released from degenerating cell membranes after nerve cell loss, thus stimulating astrocytes to synthesise ApoE, which binds these excess lipids and distributes them appropriately for reuse in cell membrane biosynthesis. 47 This observation prompted Klaver et al to speculate that a high degree of ApoE biosynthesis is required to support the high rate of photoreceptor renewal in the macular region. 47 Indeed, it has been demonstrated that mice, which were fed a high-fat diet, or which were deficient in ApoE, exhibit an increase in the thickness of Bruch's membrane, 62 which is seen in association with ageing and with AMD.…”
Section: Apoe and The Retinamentioning
confidence: 99%